Research on Groove Method to Suppress Stall in Pump Turbine - Yong Liu; Hongjuan Ran; Dezhong Wang (Energies, 2020)
The pump turbine is prone to stall when running at part-load operation. Stalls would cause a hump-like head characteristic curve, low-frequency high-amplitude pressure pulsation, and surge or resonance in the system. There is a lack of efficient methods for pump turbine stall suppression. The traditional blade hydrodynamic optimization method has limited effect and would influence the other characteristics. As the essence of stall is flow separation, forming a severe backflow vortex, a “Groove Method” is put forward and employed to suppress stall in a pump turbine with the full consideration of the mechanical structure, flow field, and pressure field. Both experiments and calculations are carried out to test the effectiveness of this new method. Furthermore, its deep mechanisms are revealed. This method can weaken the head hump to a certain extent and reduce the pressure pulse amplitude induced by stall. Meanwhile, the performance at the design operating point is not disturbed much.